Manajemen Kepala Madrasah dalam Mengembangkan Kualitas Pendidikan - Hasan Luthfi, Moh; Fathor Rosi; Badri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study aims to analyze the management of the principal in improving the quality of education at MTs Nurul Huda Campalok Jatisari, Arjasa Situbondo, which faces rural-specific challenges such as limited infrastructure, strong local cultural influences, and low student learning motivation. Employing a qualitative narrative study, data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s model with credibility, transferability, dependability, and confirmability tests. The findings reveal that the principal plays a strategic role through visionary planning, organizational management of teachers and facilities, implementation of student and teacher development programs, and continuous evaluation to foster educational improvement. Specific strategies include optimizing limited resources, strengthening student discipline through motivational approaches, innovating extracurricular talent and interest programs, managing financial resources effectively, and building intensive collaboration with the community and religious leaders. The results indicate that participatory and adaptive leadership creates positive impacts such as increased teacher motivation, improved student discipline and achievement, and the establishment of a more conducive learning environment. The study concludes that the principal’s role is critical in enhancing educational quality in rural areas. The recommendation emphasizes the development of contextual, innovative, and collaborative leadership models to enable rural madrasahs to achieve competitiveness while preserving the social and cultural identity of their communities.